Determinan kualitas tidur pada lansia daerah pesisir dan dataran tinggi di kabupaten Aceh Besar - Sri Alna Mutia; Radhiah Zakaria; Hermansyah Hermansyah; Asnawi Abdullah; Nurjannah Nurjannah (Holistik Jurnal Kesehatan, 2024)
Background: Sleep quality is one of the most common problems in the elderly. Many factors cause sleep disorders, such as psychological factors, non-communicable diseases, physical activity, diet and the environment. The environment plays a big role in the occurrence of sleep disorders in a person. Places such as coastal areas and highlands provide a comfortable atmosphere to live in. Purpose: To determine the determinants of sleep quality in elderly people in coastal and highland areas. Method: Quantitative research with analytical design and cross-sectional approach was conducted on March 17-May 17, 2022 in Aceh Besar Regency. The sample used was elderly aged 60-74 years, obtained as many as 168 respondents who live in the work area of ​​the Mesjid Raya Health Center (Pesisir) and 128 elderly people in the work area of ​​the Lembah Seulawah Health Center (Highlands). The total sample was 296 people obtained using the accidental sampling technique. Data collection was carried out using questionnaires and the results of checking the integrated development post book. Results: The most dominant regional factor related to the sleep quality of the elderly after adjusting for marital status is the coastal area (p=0.000; OR=2.66). The most dominant comorbid disease factor related to sleep quality in the elderly after adjusting for marital status was gout (p=0.000; OR=4.13). The mental health disease factor that is most dominantly related to the sleep quality of the elderly after adjusting for marital status is anxiety (p=0.000; OR=3.37). The most dominant physical factor related to sleep quality in the elderly after adjusting for marital status was moderate pain (p=0.000; OR=12.72). Apart from that, there was no relationship between perpetuating factors and sleep quality in the elderly (p=0.837; QR=0.83). Conclusion: There is a relationship between the area of ​​residence and the quality of sleep in the elderly. Comorbid disease factors, mental health, and physical health are related to the quality of sleep in the elderly. However, perpetuating factors have no relationship to the quality of sleep in the elderly who live in coastal and highland areas. Suggestion: Health workers should conduct regular checks on the elderly either during posbindu activities or home visits. In addition, it is hoped that health workers will also carry out interventions such as counseling, elderly gymnastics, or relaxation in improving the health and fitness of the elderly.   Keywords: Coastal; Elderly; Highlands; Sleep Quality.   Pendahuluan: Kualitas tidur menjadi salah satu masalah yang paling sering terjadi pada lansia. Banyak faktor yang menyebabkan gangguan tidur, seperti faktor psikologis, penyakit tidak menular, aktivitas fisik, pola makan, dan lingkungan. Lingkungan memegang peran yang besar terhadap terjadinya gangguan tidur seseorang. Tempat seperti daerah pesisir pantai dan dataran tinggi memberikan suasana yang nyaman untuk ditempati. Tujuan: Untuk mengetahui determinan kualitas tidur pada lansia daerah pesisir dan dataran tinggi. Metode: Penelitian kuantitatif dengan desain analitik dan pendekatan cross sectional dilakukan tanggal 17 Maret-17 Mei 2022 di Kabupaten Aceh Besar. Sampel yang digunakan adalah lansia berusia 60-74 tahun, diperoleh sebanyak 168 responden yang tinggal di wilayah kerja Puskesmas Mesjid Raya (Pesisir) dan 128 orang lansia di wilayah kerja Puskesmas Lembah Seulawah (Dataran Tinggi). Total sampel sebanyak 296 orang yang diperoleh menggunakan teknik accidental sampling. Pengumpulan data dilakukan dengan menggunakan kuesioner dan hasil pemeriksaan buku posbindu. Hasil: Faktor wilayah yang paling dominan berhubungan dengan kualitas tidur lansia setelah disesuaikan dengan status perkawinan adalah wilayah pesisir (p=0.000; OR=2.66). Faktor penyakit komorbid yang paling dominan berhubungan dengan kualitas tidur lansia setelah disesuaikan dengan status perkawinan adalah asam urat (p=0.000; OR=4.13). Faktor penyakit kesehatan mental yang paling dominan berhubungan dengan kualitas tidur lansia setelah disesuaikan dengan status perkawinan adalah kecemasan (p=0.000; OR=3.37). Faktor fisik yang paling dominan berhubungan dengan kualitas tidur lansia setelah disesuaikan dengan status perkawinan adalah nyeri sedang (p=0.000; OR=12.72). Selain itu, tidak ada hubungan faktor perpetuating dengan kualitas tidur lansia (p=0.837; QR=0.83). Simpulan: Ada hubungan antara daerah tempat tinggal dengan kualitas tidur lansia. Faktor penyakit komorbiditas, kesehatan mental, dan fisik memiliki hubungan dengan kualitas tidur lansia yang tinggal di daerah pesisir dan dataran tinggi. Namun faktor perpetuating tidak memiliki hubungan dengan kualitas tidur lansia yang tinggal di daerah pesisir dan dataran tinggi. Saran: Petugas kesehatan agar melakukan pemeriksaan secara berkala pada lansia baik pada kegiatan posbindu atau kunjungan rumah. Selain itu, diharapkan petugas kesehatan juga melakukan intervensi seperti penyuluhan, senam lansia, atau relaksasi dalam meningkatkan kesehatan, dan kebugaran lansia.   Kata Kunci: Dataran Tinggi; Kualitas Tidur; Lansia; Pesisir.